Адміністративно-запобіжні заходи у діяльності Державної служби України з лікарських засобів та контролю за наркотиками: питання сьогодення - Птухіна, О. В.; Ptukhina, O. V. (Наше право. - 2023. - № 2. - С. 80-87, 2023)
Наголошено, що адміністративно-запобіжні заходи виконують свої особливі правоохоронні функції, які відрізняють їх від інших заходів адміністративного примусу, що і визначає їх самостійне місце в системі цих заходів. Доведено, що під адміністративно-запобіжними заходами в діяльності Держлікслужби України слід розуміти сукупність засобів одностороннього офіційно-владного впливу останньої, урегульованих нормами адміністративного права, щодо фізичних та юридичних осіб і спрямовані на попередження порушень норм законодавства у сферах контролю якості та безпеки лікарських засобів, медичних виробів, обігу наркотичних засобів, психотропних речовин і прекурсорів, протидії їх незаконному обігу, донорства крові та компонентів крові, функціонування системи крові, які полягають у недопущенні протиправної поведінки з боку конкретних (фізичних та юридичних) осіб та усуненні причин, що сприяють вчиненню порушень законодавства у зазначених сферах і створення умов, що виключають протиправну поведінку.

The scientific article carried out a scientific analysis of the positions of scientists regarding the understanding of administrative preventive measures in the activities of public administration bodies in order to observe the basic rights and freedoms of a person and a citizen. Attention is drawn to the fact that by applying administrative and preventive measures, officials of the State Medical Service of Ukraine thereby create the necessary conditions for strict compliance with laws, detection and termination of various violations of legislation on ensuring the quality of medicines and medical devices, and avert possible encroachments on public relations protected by law. It is emphasized that administrative preventive measures perform their special law enforcement functions, which distinguish them from other measures of administrative coercion, which determines their independent place in the system of these measures. It has been proven that administrative and preventive measures in the activity of the State Medical Service of Ukraine should be understood as a set of means of unilateral official-authority influence of the latter, regulated by the norms of administrative law, in relation to individuals and legal entities and aimed at preventing violations of legislation in the areas of quality control and safety of medicinal products, medical products, circulation of narcotic drugs, psychotropic substances and precursors, combating their illegal circulation, donation of blood and blood components, functioning of the blood system, which consist in preventing illegal behavior on the part of specific (natural and legal) persons and eliminating the causes that contribute to violations of the law in the specified areas and creating conditions that exclude illegal behavior. It was emphasized that administrative and preventive measures are implemented by the State Medical Service of Ukraine, taking into account the main directions of the latter’s activities: 1) measures regarding licensing of production, import of medicinal products, monitoring of compliance with licensing conditions and certification; 2) measures regarding state regulation of wholesale and retail trade in medicinal products; 3) measures on issues of state market supervision; 4) measures to ensure state quality control of medicinal products; 5) measures regarding state regulation and control in the sphere of circulation of narcotic drugs, psychotropic substances, precursors and combating their illegal circulation.

Отмечено, что административно-мероприятия выполняют свои особые правоохранительные функции, которые отличают их от других мер административного принуждения, что и определяет их самостоятельное место в системе этих мер. Под административно-предупредительными мерами в деятельности Гослекслужбы Украины следует понимать совокупность средств одностороннего официально-властного влияния последней, урегулированных нормами административного права, в отношении физических и юридических лиц и направленные на предупреждение нарушений норм законодательства в сферах контроля качества и безопасности лекарственных средств, медицинских изделий, обращения наркотических средств, психотропных веществ и прекурсоров, противодействия их незаконному обращению, донорства крови и компонентов крови, функционирования системы крови, которые заключаются в недопущении противоправного поведения со стороны конкретных (физических и юридических) лиц и устранении причин, способствующих совершению нарушений законодательства в указанных сферах и создание условий, исключающих противоправное поведение.
Administrative and preventive measures in the activities of the State Service of Ukraine on Drugs and Drug Control: today’s issues
Птухіна, О. В. Адміністративно-запобіжні заходи у діяльності Державної служби України з лікарських засобів та контролю за наркотиками: питання сьогодення / Птухіна Олена Валеріївна // Наше право. - 2023. - № 2. - С. 80-87. - DOI: 10.32782/NP.2023.2.10.
Keywords: Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Державна служба України з лікарських засобів та контролю за наркотиками; State Service of Ukraine for Medicinal Products and Drug Control; Государственная служба Украины по лекарственным средствам и контролю за наркотиками; адміністративно-запобіжні заходи; administrative preventive measures; административно-предупредительные меры; контроль за якістю лікарських засобів; quality control medicines; контроль за качеством лекарственных средств; повноваження; powers; полномочия